Reddish-orange emitting Eu2−xGdxGe2O7 pyrogermanate ceramic phosphors: synthesis and role of Eu3+/Gd3+ substitution on the optical features - Martins, Guilherme M; Caixeta, Fábio J [UNESP]; de Souza, Vitor Dos S; Gonçalves, Rogéria R; Dias, Anderson (IOP Publishing, 2024)
In this work, highly luminescent pyrogermanates were successfully synthesized through the solid-state reaction route, and the role of gradual Eu3+ substitution for Gd3+ on the structure and photoluminescent properties of Eu2−x Gd x Ge2O7 pyrogermanates was investigated. Pure Eu2Ge2O7 ceramic is triclinic, belonging to the P1 (#1) space group, and by increasing the x values, the crystal structure changes with the partial substitution of Eu3+ ions by the Gd3+ ions into the chemical lattice. The other phase-pure ceramic, Gd2Ge2O7, belongs to the tetragonal P41212 (#92) space group. Complete solid solubility was attained for x ⩽ 1.6, where Gd3+ replaced Eu3+ in the triclinic structure. It was verified that the band gap energies are dependent on the crystalline structure, increasing as Gd replaced Eu in the Eu2−x Gd x Ge2O7. The lowest band gap value (5.13 eV) was observed for the triclinic Eu2Ge2O7, and the highest one (5.88 eV) for the tetragonal Gd2Ge2O7. Highly intense reddish-orange emission (quantum efficiency up to 91.9%), through excitation at charge transfer band and Ln3+ f-f transitions were evaluated as the Gd substitution rises. Substitution-sensitive phase change at the nanoscale was monitored by Eu3+ emission, validating the presence of Eu3+ in the triclinic and/or tetragonal phase depending on the chemical composition (or the Gd3+/Eu3+ ratio). The chromaticity diagram figured out a reddish-orange emission, making them promising materials for high-entropy and photonic devices as solid-state lighting using excitation by near UV light-emitting devices.
Keywords: band gap; europium; gadolinium; photoluminescence properties; pyrogermanates; solid solutions; structural phase transformation